Considerations Regarding CHSY1 Knockdown and Its Influence on Gene Expression Profiles: A Perspective from Protein Interaction Network Analysis - Zamanian-Azodi, Mona; Ahmadzadeh, Alireza; Rezaei, Mitra; Robati, Reza M (Asian Pacific Journal of Cancer Biology, 2024)
Introduction: Knockdown of CHSY1 in ovarian cancer holds promise for monitoring tumorigenesis and the application of targeted therapies. Method: A comparison was made between microarray datasets of ovarian cancer with and without CHSY1 knockdown to identify differentially expressed genes (DEGs). Subsequently, the DEGs were analyzed using Cytoscape and its plug-ins. All key genes in the protein-protein interaction (PPI) network originated from the expression dataset which exhibiting significant differential expressions. Result: Particularly PTEN, STAT3, BRCA, CCND1, and HIST1H4I emerged as central hub-bottlenecks within the PPI network following CHSY1 knockdown. Conclusion: This compilation suggests that the candidate genes and their associated biological processes may have substantial connections to the effects of knockdown, inhibiting some cancer-related genes to prevent cancer progression.